Analysis of COL1A1_1 gene (rs1107946) polymorphism as a risk factor for low birth weight - Shumna, T. Ye.; Levchuk, T. O.; Kamyshnyi, O. M.; Шумна, Таміла Євгенівна; Левчук, Тетяна Олегівна; Камишний, Олександр Михайлович; Шумная, Т. Е.; Левчук, Т. О.; Камышный, А. М. (Запорізький державний медичний університет, 2019)
Objective. Identification of the CA genotype of the (rs1107946) polymorphism of COL1A1_1 gene and the pattern of allele dis¬tribution in low birth weight babies. Materials and methods. A total of 168 babies were examined. The babies were divided into 3 groups depending on the birth weight: the 1st group comprised of 52 babies (birth weight was 1500–1999 g), the 2nd group – 76 babies (birth weight was 2000– 2499 g) and the 3rd group – 40 babies (birth weight was more than 2500 g, that is they had normal birth weight). Polymerase chain reaction genotyping method was used. Мета роботи – визначення генотипів поліморфізму С/А гена колагену COL1A1_1 (rs1107946) і закономірність розподілу алельних генів у дітей із малою масою тіла при народженні. Матеріали та методи. Обстежили 168 дітей. Пацієнтів поділили на 3 групи залежно від ваги при народженні: І група – 52 дітей (вага при народженні становила 1500–1999 г), ІІ – 76 дітей (вага при народженні – 2000–2499 г), ІІІ – 40 дітей (вага при народженні – понад 2500 г, тобто нормальна маса тіла). Генотипування здійснили методом полімеразної ланцюгової реакції. Цель работы – определение генотипов полиморфизма С/А гена коллагена COL1A1_1 (rs1107946) и закономерность распределения аллельных генов у детей с малой массой тела при рождении. Материалы и методы. Обследовали 168 детей. Пациентов поделили на 3 группы в зависимости от веса при рождении: І группа – 52 детей с весом при рождении 1500–1999 г, ІІ группа – 76 детей с весом при рождении 2000–2499 г, ІІІ груп па – 40 детей с весом при рождении 2500 г и более (с нормальной массой тела). Генотипирование проводили методом полимеразной цепной реакции.
Аналіз поліморфізму гена COL1A1_1 (rs1107946) як фактора ризику народження дітей з малою масою тіла
Анализ полиморфизма гена COL1A1_1 (rs1107946) как фактор риска рождения детей с низкой массой тела
Keywords: allelic genes; genotyp; collagen; thinness; babies; алельні гени; генотипи; колаген; низька вага; діти; аллельные гены; генотипы; коллаген; низкий вес; дети